XRCC1 counteracts poly(ADP ribose)polymerase (PARP) poisons, olaparib and talazoparib, and a clinical alkylating agent, temozolomide, by promoting the removal of trapped PARP1 from broken DNA. (1st March 2022) - Hirota, Kouji; Ooka, Masato; Shimizu, Naoto; Yamada, Kousei; Tsuda, Masataka; Ibrahim, Mahmoud Abdelghany; Yamada, Shintaro; Sasanuma, Hiroyuki; Masutani, Mitsuko; Takeda, Shunichi
Abstract: Base excision repair (BER) removes damaged bases by generating single‐strand breaks (SSBs), gap‐filling by DNA polymerase β (POLβ), and resealing SSBs. A base‐damaging agent, methyl methanesulfonate (MMS) is widely used to study BER. BER increases cellular tolerance to MMS, anti‐cancer base‐damaging drugs, temozolomide, carmustine, and lomustine, and to clinical poly(ADP ribose)polymerase (PARP) poisons, olaparib and talazoparib. The poisons stabilize PARP1/SSB complexes, inhibiting access of BER factors to SSBs. PARP1 and XRCC1 collaboratively promote SSB resealing by recruiting POLβ to SSBs, but XRCC1 −/− cells are much more sensitive to MMS than PARP1 −/− cells. We recently report that the PARP1 loss in XRCC1 −/− cells restores their MMS tolerance and conclude that XPCC1 facilitates the release of PARP1 from SSBs by maintaining its autoPARylation. We here show that the PARP1 loss in XRCC1 −/− cells also restores their tolerance to the three anti‐cancer base‐damaging drugs, although they and MMS induce different sets of base damage. We reveal the synthetic lethality of the XRCC1 −/− mutation, but not POLβ −/−, with olaparib and talazoparib, indicating that XRCC1 is a unique BER factor in suppressing toxic PARP1/SSB complex and can suppress even when PARP1 catalysis is inhibited. In conclusion, XRCC1 suppresses the PARP1/SSB complex via PARP1 catalysis‐dependent and independent mechanisms.